Evaluation of the intrinsic thermal performance of an envelope in hot period: Outdoor experiment at a 40m3 test cell - Jay, Arnaud; Tanchou, Marie; Fares, Hafsa; Anger, Jocelyn (CLIMA 2022 conference, 2022)
Ensuring the proper thermal performance of a building’s envelope upon reception is an important stage in the life cycle of the building. Several methods already exist for this purpose, and continue to be improved, such as co-heating, ISABELE, EPILOG, QUB and SEREINE. All these methods follow the common protocol consisting of heating the measured building with an electrical system. These measurement protocols quantify the dynamic evolution of interior and outdoor temperatures, and the thermal power injected into the building. These data are used in calibration algorithms to determine, by an inverse method, a heat loss value. These methods require a difference of a few degrees between the interior and the exterior which can cause in summer periods a risk of damaging the building, as the outside temperature may already be high. The objective of this work is to explore the possibility of determining the intrinsic thermal performance of a building’s envelope in the summer period using a cooling hydraulic system. Some encouraging experiments have been done on a square meter scale cell in an indoor environment. The focus of this paper is to test a similar method in an outdoor Passys test cell of 40m3 and explore the capacities and limitations of the method at this scale by varying several stress parameters of the enclosure. First, some electrical heating modes are run acting as reference values. Then, a hydraulic system is used to estimate the HLC value and gives comparable results to the electrical mode considering an uncertainty of 2 W/K. Third step is to setup cooling scenario with the hydraulic system. Some of the results are also comparable with the heating mode and some limits are highlighted such as the cooling power limitation to avoid water condensation into the cell. This impact of condensation is then studied and seems to have a limited impact on the results for this experiment.